Factors Associated With COVID-19 Vaccine Hesitancy and Preferred Sources of Health Information Among Medically Underserved Populations in North Carolina - Celeste R. Gracey; Godwin Y. Dogbey; David R. Tillman; Amy N. Hinkelman (North Carolina Medical Journal, 2026)
BACKGROUND Despite vaccines being one of the most effective tools for preventing severe disease caused by infections such as COVID-19, vaccine hesitancy is a growing concern. Vaccine uptake among rural communities has lagged behind urban areas, and factors associated with vaccine hesitancy among individual communities can vary. METHODS An online Qualtrics survey was developed using principles from the World Health Organization (WHO) to identify demographic, modifiable (e.g., confidence-related attitudes, trusted information sources), and non-modifiable (e.g., age, education, health care worker status) risk factors associated with COVID-19 vaccine hesitancy among rural, underserved populations of North Carolina using a multivariate logistic regression. We also sought to identify the preferred sources of health information. In this study, 918 participants from 40 counties with high health professional shortage area (HPSA) scores in primary care completed the survey and were identified as either “vaccine willing” or “vaccine hesitant.” RESULTS We determined that age, education level, having a family member seriously ill with COVID-19, and working in health care were associated with willingness to vaccinate. Free-response questions revealed safety as the top concern for vaccine-hesitant participants, who expressed concerns for long- and short-term side effects and even death from the vaccines. Convenience played a very limited role in vaccine behavior. Health care professionals were identified as the most trusted source of health care information and preferred resource for learning more about vaccines. LIMITATIONS Self-reported data limited to English speakers with access to technology alongside the evolving nature of vaccine attitudes may not fully represent current attitudes in these counties. CONCLUSIONS Vaccine hesitancy among rural, underserved North Carolina populations is related to modifiable and non-modifiable risk factors. Trust in health care providers for reliable health information including vaccines remained high even among those who were vaccine hesitant, suggesting provider-led, trust-building vaccination outreach in rural settings.